U.S. trust in physicians as key public health messengers during the H5N1 avian influenza outbreak - Rachael Piltch-Loeb; Shawn G. Gibbs; John J. Lowe; Sara Gorman; Katarzyna Wyka; Trenton M. White; Ayman El-Mohandes (Scientific Reports)
Abstract The emerging threat of H5N1 avian influenza in humans has renewed the need for effective public health communication strategies, especially in light of reduced public trust in governmental institutions. During recent health crises, personal healthcare providers, particularly physicians, have emerged as the most trusted sources of information, surpassing institutions like the CDC and local health departments. This study explores the role of physicians as key messengers for health information related to H5N1 risk, vaccine guidance, and interventions among the U.S. population. A nationally representative survey of U.S. adults was conducted from August 5–15, 2024, employing phone, text, and online panels. Respondents were asked about trusted sources of health information and preferred vaccine advisors, along with sociodemographic variables. Weighted logistic regressions were used to identify associations between trust in messengers and sociodemographic factors, with results stratified by urban and rural populations. Physicians were the most trusted messengers for health information (76.2%), followed by personal research (36.7%) and local/state health departments (32%). Vaccine advice was most frequently sought from physicians (53.0%), with substantial differences in trust and advice preferences based on age, income, ethnicity, and political affiliation. Notably, trust in physicians was lower among Black and Hispanic respondents compared to White respondents, highlighting disparities in public trust. Physicians play a crucial role in public health communication for emerging threats like H5N1, especially given diminished trust in institutional sources. Effective communication strategies should leverage physicians’ trusted status while addressing demographic differences in trust to enhance public engagement and adherence to health advisories across diverse communities.